The Role of Throat Packs in Orthognathic Surgery—A Systematic Review and Meta-Analysis - Mehul Saha; Anupam Singh; Kalyana Chakravarthy Pentapati; Srikanth Gadicherla; Chithra Aramanadka; Adarsh Kudva (The Scientific World Journal)
Orthognathic surgery entails a high risk of blood ingestion, which causes postoperative nausea and vomiting (PONV). Throat packs are placed to combat this problem. However, the efficacy of throat packs in reducing blood ingestion and PONV is debatable. We aimed to review the existing literature and pool the estimates of the quality of gastric contents, PONV, and throat pain associated with and without the use of throat packs among patients undergoing orthognathic surgery. Globally recognized databases (PubMed, Scopus, Embase, CINAHL, and Web of Science) were searched to identify relevant studies, and 2 randomized controlled trials comprising 84 participants were included. A qualitative analysis of the gastric contents showed that throat packs are not practical barriers against the ingestion of blood during orthognathic surgery. The meta-analysis revealed that placement of throat packs during orthognathic surgery did not reduce the incidence of PONV (p value = 1) and caused higher postoperative throat pain (p value = 0.02). Thus, the current review provides no evidence in favor of throat packs during orthognathic surgery. The role of throat packs in preventing blood ingestion is questionable due to a limited number of studies. They play no significant role in preventing PONV and increase postoperative throat pain.